Vertical profiles of sediment methanogenic potential and communities in two plateau freshwater lakes - Yang, Yuyin; Li, Ningning; Wei Wang; Li, Bingxin; Xie, Shuguang; Yong Liu (BIOGEOSCIENCES, 2017)
Microbial methanogenesis in sediment plays a crucial role in CH4 emission from freshwater lake ecosystems. However, knowledge of the layer-depth-related changes of methanogen community structure and activities in freshwater lake sediment is still limited. The present study was conducted to characterize the methanogenesis potential in different sediment-layer depths and the vertical distribution of microbial communities in two freshwater lakes of different trophic status on the Yunnan Plateau (China). Incubation experiments and inhibitor studies were carried out to determine the methanogenesis potential and pathways. 16S rRNA and mcrA genes were used to investigate the abundance and structure of methanogen and archaeal communities, respectively. Hydrogenotrophic methanogenesis was mainly responsible for methane production in sediments of both freshwater lakes. The layer-depth-related changes of methanogenesis potential and the abundance and community structure of methanogens were observed in both Dianchi Lake and Erhai Lake. Archaeal 16S rRNA and mcrA genes displayed a similar abundance change pattern in both lakes, and the relative abundance of methanogens decreased with increasing sediment-layer depth. Archaeal communities differed considerably in Dianchi Lake and Erhai Lake, but methanogen communities showed a slight difference between these two lakes. However, methanogen communities illustrated a remarkable layer-depth-related change. Order Methanomicrobiales was the dominant methanogen group in all sediments, while Methanobacteriales showed a high proportion only in upper layer sediments. The trophic status of the lake might have a notable influence on the depth-related change pattern of methanogenesis activity, while the methanogen community structure was mainly influenced by sediment depth.